Recommended 5G frequency bands evaluation - Tikhomirov, Andrey; Omelyanchuk, Elena; Semenova, Anastasia (2018 Systems of Signals Generating and Processing in the Field of on Board Communications, 2018)
For the development of mobile communication systems of fifth generation (5G) a number of frequency bands are currently proposed in Russian Federation. Since the 5G standard does not yet exist and the requirements for 5G systems are very wide, a detailed analysis is needed to select the frequency band for 5G networks. The article presents the main problems that should be solved in order to implement 5G and whether its requirements can be achieved in the recommended frequency bands. Evaluation of the possibility of using each band was made with regard to the corresponding problems, system goals and link budget estimation. MmWaves may be recommended for the stationary network devices, while for mobile services it is proposed to use frequencies below 6 GHz.